Aplikasi Pupuk Hayati Mikoriza terhadap Tanaman Bawang Merah (Allium cepa var. aggregatum) pada Latosol Dramaga: Application of Mycorrhizal Biofertilizer on Shallot (Allium cepa var. aggregatum) Plant on Latosol Dramaga - Fahrizal Hazra; Fatimah Nur Istiqomah; Lusiana Adriani (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Mycorrhizal bio-fertilizers can maintain land productivity and are environmentally friendly. This study aims to analyze the effect of mycorrhizal biofertilizer on the growth of shallots (Allium cepa var. Aggregatum) and to determine root infection and its effect on soil N, P, K levels. The experimental design used was a completely randomized design (CRD). The treatment of biological fertilizer testing is carried out based on the Regulation of the Minister of Agriculture No. 70 / Permentan / SR. 140/10/2011, consisting of 6 treatments (AF) as follows: A) control, B) standard fertilizers, C) mycorrhizal biological fertilizers, D) mycorrhizal biological fertilizers + 25% standard fertilizers, E) mycorrhizal biological fertilizers + 50% standard fertilizer, F) mycorrhizal biological fertilizer + 75% standard fertilizer. There were 5 replications so that 30 experimental units were obtained. Mycorrhizal bio-fertilizers can reduce the need for standard fertilizers (PS) to 25% to 50%. The combination of biological fertilizer of 2.5 g / plant with 50% PS produces the best plant height and biomass weight, but economically it is recommended to use 25% PS. The treatment applied to mycorrhizae had a very high root infection value, which was above 75%. The types of spores that were successfully associated were Acaulospora sp., Glomus etunicatum, and Glomus sp. The application of mycorrhizae resulted in an increased response of 14.91% for P-available Latosol, while for K-dd and N-total there was no significant effect.